DSP-based implementation of fast terminal synergic control for a DC-DC Buck converter, ISSN / e-ISSN 0016-0032 / 1879-2693 - Zerroug Nadjat; Harmas Mohamed Naguib; Bouchama Ziyad; Benaggoune Said; Zehar Khaled (Journal of the Franklin Institute, 2018)
Finite time convergence based on robust synergetic control (SC) theory and terminal attractor techniques is investigated. To this end a fast terminal synergetic control law (FTSC) is applied to drive a DC–DC Buck converter via simulation and through a dSpace based experimental setup to validate the approach. As robust as sliding mode control, the synergetic approach used is chattering free and provides rapid convergence. Efficacy of the proposed fast terminal synergetic controller is tested for step load change and output voltage variation and results compared to classical synergetic and PI control. Experimental validation using dSpace DS1104 confirms the results obtained in simulation showing the soundness of this approach compared to synergetic and PI controllers.